The Effects of the Developments in Artificial Intelligence and Open-Access Software on the Visions of Academicians - BATAKLAR, SİNAN; DEVECİYAN, MERİ TAKSİ (Brill Academic Publishers, 2024)
This research aims to examine the effects of developments in Artificial Intelligence (AI) and open-access software on the visions of academicians. The research was conducted using the phenomenology pattern, one of the qualitative research methods, and semi-structured in-depth interviews were preferred during the data collection process. Descriptive and coding-based qualitative content analysis methods were used in the research process. Emerging themes include the use of artificial intelligence in higher education; situation analysis of the use of AI in academics (SWOT); and strategic dimension of using AI in higher education. These themes explain in detail the potential effects of AI and open-access software on the strategy and competitiveness dimensions of academics’ visions. It is expected that the study will make significant contributions to understanding the changes that AI and open-access software will create in the academic world and how these technologies can be integrated into the way academics work.
Keywords: Artificial Intelligence; Higher Education; Open-access Software; SWOT Analysis; Visions of Academicians